Women in Martial’s eyes - Beraldo Santana do Amaral da Rocha, Mariana (Romanitas - Revista de Estudos Grecolatinos, 2019)
In approximately 25% of his epigrams, of more than 1500, Martial presents the female gender as subject of the epigrammatic narrative, however, the poet varies the tone used in each narrated character. Now the poet points out an addiction, sometimes he throws mythological or historical themes, sometimes some consecrated person echoes, sometimes some woman who is part of the poet’s personal life is remembered by him, for example. Although they appear throughout Epigrammata, most of them are in books I, VIII, X, XII. Here, in this article, it was selected some types described by Martial, it is our aim to present the translation of these, in a panorama of how women were seen in First Century AD Rome.